PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP PRODUTIVITAS KERJA DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL INTERVENING STUDI PADA KARYAWAN PT. SOCFINDO KEBUN NEGERI LAMA - Safira Ulya Nurid; Zulkarnain Nasution; Meisa Fitri Nasution (Politeknik Bisnis Indonesia, 2022)
This research aims to analyze the influence of occupational safety and health on work productivity with organizational commitment as an intervening variable in PT Socfindo Perkebunan Negeri Lama. The research is explanatory in nature and intended to explain the relation between variabels.. The Population of this research involves regular employees of PT Socfindo Perkebunan Negeri Lama. The sample consists of 78 employees taken by using proportional random sampling. Further, the data were analysed with descriptive measure and path analysis using SPSS 23. It is found that (1) occupational safety and health have a directly influenced work productivity (2) occupational safety and health directly influenced organizational commitments (3) organizational commitments directly affect work productivity. (4) occupational safety and health indirectly affect work productivity through organizational commitment.